2021
DOI: 10.1055/s-0041-1729754
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cancer-Associated Venous Thrombosis: A Nationwide Survey among Danish Oncologists

Abstract: Background Treatment patterns for cancer-associated venous thrombosis (CAT) has been shown to be nonconsistent with contemporary guideline recommendations, resulting in poor patient outcomes. Objectives The study aimed to describe contemporary CAT management in Danish oncology departments and identify knowledge gaps and inconsistencies between guidelines and clinical practice. Patients and Methods A survey questionnaire in Danish was developed based on contemporary national guidelines. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…An option for primary outpatient thromboprophylaxis with low-molecular-weight heparin was introduced in Danish guidelines in 2017 but is not used in clinical practice. 40,42,56 Restricting the study period to before 2017 also revealed similar risk estimates, indicating that the use of low-molecular-weight heparin in the most recent years did not contribute to lowering risk estimates.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…An option for primary outpatient thromboprophylaxis with low-molecular-weight heparin was introduced in Danish guidelines in 2017 but is not used in clinical practice. 40,42,56 Restricting the study period to before 2017 also revealed similar risk estimates, indicating that the use of low-molecular-weight heparin in the most recent years did not contribute to lowering risk estimates.…”
Section: Discussionmentioning
confidence: 77%
“… 38,39 However, due to uncertainties about the net clinical benefit, mainly related to bleeding risk, guideline recommendations remain vague, and primary thromboprophylaxis is therefore rarely used in clinical practice. 40-43 …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of both venous thrombosis, bleeding, and recurrent venous thrombosis is high, thereby complicating the decisions on treatment and secondary prophylaxis [ 63 , 64 , 65 ]. Adding to this, the treatment decisions are often taken by the treating oncologist or hematologist without their consultancy with a thrombosis specialist [ 66 ]. The guidelines typically recommend a minimum of 6 months of an anticoagulation treatment after cancer-associated venous thromboembolism [ 61 ].…”
Section: Recommendations For Specific Populationsmentioning
confidence: 99%